Portable Document Format (PDF): Standardizing Document Files for Publication - Craft, John R. (DESIDOC Journal of Library & Information Technology, 2003)
Just a few years ago, publishers used to send camera-ready copies of their manuscripts to printers who then used process cameras to copy those pages onto film, make proofs, create plates, and print the books. That scenario has now completely changed. Publishers are presently sending what would be considered ‘print-ready’ manuscripts files on diskettes or CD-ROMs or uploading the files electronically to commercial printing companies. The printing companies work with those files in creating proofs and producing the final products. In this scenario, the Portable Document Format (PDF) is playing a significant role in the production and distribution of both electronic and printed books. The PDF is emerging as a stable standard file format for the publishing industry. http://dx.doi.org/10.14429/dbit.23.1.3587